FASILITAS GEDUNG BAGI MASYARAKAT BERKEBUTUHAN KHUSUS (DISSABILITAS) MENURUT UU No. 28 TAHUN 2002 TENTANG BANGUNAN GEDUNG - Rohani, Siti (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
This paper discusses the existing building facilities in the city of Pontianak both office buildings and public buildings. Under Law No. 28 of 2002 on Building provide legal protection for people with special needs (disabilities). In this Act gives liability for building owners to provide support facilities for the people of Disability in activities in the building which was to come. Facilities that can be provided by the building owner from providing a way for wheelchair users, special toilets, a special lift and others. Occurred despite the fact that the Act has required the building owner to build the facilities needed by persons with disabilities, but not all building owners meet what was required in the law.